2020
DOI: 10.1101/2020.08.24.264077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human ACE2 peptide mimics block SARS-CoV-2 Pulmonary Cells Infection

Abstract: In the light of the recent accumulated knowledge on SARS-CoV-2 and its mode of human cells invasion, the binding of viral spike glycoprotein to human Angiotensin Converting Enzyme 2 (hACE2) receptor plays a central role in cell entry. We designed a series of peptides mimicking the N-terminal helix of hACE2 protein which contains most of the contacting residues at the binding site and have a high helical folding propensity in aqueous solution. Our best peptide mimics bind to the virus spike protein with high af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Recombinant soluble human ACE2 fused to the Fc region of the human immunoglobulin IgG1 to increase short half-life of soluble ACE2 ( Iwanaga et al, 2020 ; Lei et al, 2020 ) and human recombinant soluble ACE2 ( Monteil et al, 2020 ) have been shown to inhibit SARS-CoV-2 infection in cell lines, engineered human blood vessels and kidney organoids. Recently, peptides mimicking the N-terminal helix of the human ACE2 protein, which contains most of the contacting residues for the S protein-binding site, were shown to block infection of human pulmonary cells with SARS-CoV-2, with IC 50 values in the range of 60-800 nM ( Karoyan et al, 2020 ). Similarly, ACE2 peptides optimized to SARS-CoV-2 spike protein binding regions using protein-engineering methods potently bound to the spike protein with a 170-fold higher affinity than wild-type ACE2 and inhibited SARS-CoV-2 infection (IC 50 of 28 ng/ml) in cell lines ( Glasgow et al, 2020 ).…”
Section: Antiviral Agents and Other Drugs On Ace2mentioning
confidence: 99%
“…Recombinant soluble human ACE2 fused to the Fc region of the human immunoglobulin IgG1 to increase short half-life of soluble ACE2 ( Iwanaga et al, 2020 ; Lei et al, 2020 ) and human recombinant soluble ACE2 ( Monteil et al, 2020 ) have been shown to inhibit SARS-CoV-2 infection in cell lines, engineered human blood vessels and kidney organoids. Recently, peptides mimicking the N-terminal helix of the human ACE2 protein, which contains most of the contacting residues for the S protein-binding site, were shown to block infection of human pulmonary cells with SARS-CoV-2, with IC 50 values in the range of 60-800 nM ( Karoyan et al, 2020 ). Similarly, ACE2 peptides optimized to SARS-CoV-2 spike protein binding regions using protein-engineering methods potently bound to the spike protein with a 170-fold higher affinity than wild-type ACE2 and inhibited SARS-CoV-2 infection (IC 50 of 28 ng/ml) in cell lines ( Glasgow et al, 2020 ).…”
Section: Antiviral Agents and Other Drugs On Ace2mentioning
confidence: 99%
“…Another study used a programmatic approach to search and identification based on the hACE2 sequence of ten peptides that have a high potential for interaction with CoV-RBD [ 250 ]. Drugs targeting this mechanism are not yet available, but the recent work has demonstrated that peptide hACE2 mimics, creating from the H1 helix and consisting only of natural amino acids, block infection of human lung cells with IC50 in the nM range [ 251 ]. It is about eliminating the effect on the renin–angiotensin system and the kinin–kallikrein system in the light of the pathophysiological mechanisms associated with SARS-CoV-2 [ 252 , 253 ].…”
Section: Prediction and Development Of New Ampsmentioning
confidence: 99%
“…57, 58, 59 Due to their unique physico-chemical properties (hydrophobicity, cationic charge) enabling impact to viruses prior to infection, HDPs are well-suited for prophylactic development, as some HDPs appear to behave in a manner similar to the neutralization of virus observed in the presence of neutralizing antibodies. 60, 61, 62, 63 Numerous recently published reports 64, 65, 66, 67, 68, 69, 70, 71, 72 support the antiviral activity of HDPs in the context of coronaviruses, 73 including SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 90%